Effect of monomers content in enhancing solid-state densification of silicon carbide ceramics by aqueous gelcasting and pressureless sintering. Issue 6 (15th April 2017) - Jana, Dulal Chandra; Sundararajan, G.; Chattopadhyay, K.
Abstract: The possibility of obtaining solid-state sintered silicon carbide (SiC) through aqueous gelcasting using commercial SiC powders was demonstrated. Green bodies were prepared from thixotropic SiC slurries in aqueous medium with optimized pH and solid-loading. The monomer system in gelcasting provides strength to the green bodies through formation of a gel network by polymerization and the carbon from polymeric gel enhances the densification of SiC, thereby avoiding addition of carbon externally to the gelcasting batches. Maximum bulk density of 3.16 g/cm 3 (98.4% of relative density) was achieved in gelcast SiC on sintering at 2150 °C in argon atmosphere. The effect of carbon on SiC densification is evinced from the changes in microstructure of sintered SiC with increase in carbon content. The density and microstructure of gelcast and sintered SiC was comparable to that obtained from dry pressing and sintering of additive mixed SiC powders.